Enhancing STEM Learning through the Activated Classroom Teaching Pedagogy: A Case Study in Primary Mathematics - Desmond Wesley Govender; Daniel Adeboye; Irene Govender (E-Journal of Humanities, Arts and Social Sciences)
Students often exhibit a strong aversion to STEM subjects, particularly Mathematics, leading to poor performance. This study thus explored the use of the Activated Classroom Teaching (ACT) pedagogy in addressing this aversion. The ACT model incorporates five core components: curation, conversation, correction, creation, and chaos—that promote active learning through technology. A seven-week intervention was conducted with 91 primary school students in Nigeria to evaluate the model’s effect on student engagement and academic performance. Data was collected through pre- and post-intervention tests. Results indicated a significant improvement in students’ performance, with an 8.79% increase in mean scores. This study highlights the potential of active digital pedagogies to transform mathematics education and improve outcomes in STEM subjects. The results of this study show that active learning strategies, especially those that leverage technology, can play a critical role in addressing the challenges associated with traditional mathematics education.